2019
DOI: 10.1080/02687038.2019.1602813
|View full text |Cite|
|
Sign up to set email alerts
|

Relations between executive function, language, and functional communication in severe aphasia

Abstract: Background: Intervention in severe aphasia often means aiming for access to meaningful social interaction in spite of linguistic barriers that might not be treatable. This demands knowledge about the different factors that influence functional communication. Apart from linguistic ability, executive functions are thought to play an important role. Aims: To expand the understanding of the relations of executive functions and linguistic ability to functional communication in severe aphasia. Methods and Procedures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 54 publications
(93 reference statements)
2
28
0
Order By: Relevance
“…There are both theoretical and empirical reasons to believe that executive function, as measured with standardised neuropsychological tests, is important to functional communication in severe aphasia [17][18][19]. However, the aspects of executive function that are important to functional communication seem not to be captured by BRIEF-A informant ratings [32].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are both theoretical and empirical reasons to believe that executive function, as measured with standardised neuropsychological tests, is important to functional communication in severe aphasia [17][18][19]. However, the aspects of executive function that are important to functional communication seem not to be captured by BRIEF-A informant ratings [32].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the results of the BRIEF-A ratings did not show any relationship to functional communication. Relationships between functional communication and executive function, when measured with neuropsychological tests, have been previously reported [17,18]. Thus, BRIEF-A does not seem to be sensitive to the aspects of executive function that are important to functional communication.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Previous research has used tests or rating scales to elucidate the relationship between functional communication and language impairments ( Irwin et al , 2002 ) and/or other cognitive impairments ( Fridriksson et al , 2006 ; Fucetola et al , 2006 ; Purdy and Koch, 2006 ; Murray, 2012 ; Meier et al , 2017 ; Olsson et al , 2019 ; Spitzer et al , 2019 ), as well as to assess or predict the outcome after stroke ( van de Sandt-Koenderman et al , 2008 ; Blom-Smink et al , 2017 ). Unsurprisingly, a close association between functional communication and the severity of the language impairment ( Fucetola et al , 2006 ; Meier et al , 2017 ), especially with phonology or speech production abilities ( Irwin et al , 2002 ; Fridriksson et al , 2006 ; Blom-Smink et al , 2017 ), is usually reported.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, some of the inconsistencies in previous findings could stem from differences between functional communication measures and their ability to grade all levels of remaining communication ability. Second, functional communication abilities have been compared with either an overall measure of verbal or non-verbal impairment severity (composite scores of several tests/screening measure; van de Sandt-Koenderman et al , 2008 ; Meier et al , 2017 ; Olsson et al , 2019 ), or to performance in individual tests ( Fridriksson et al , 2006 ; Purdy and Koch, 2006 ; Murray, 2012 ). Thus, a more detailed consideration of how functional communication relates to the different components of patients’ verbal and non-verbal cognitive profiles is needed.…”
Section: Introductionmentioning
confidence: 99%